14 Effects of sample extract methods on the production and antioxidant activity of Lepista sordida polysaccharides. (1st December 2016) - Wang, Lanying; Tang, Meng; Huang, Xiaomin; Chen, Peizhou; Lei, Xi; Hou, Ali
Abstract : Background: Polysaccharides, one of the main bioactive compounds in natural resources such as fungi, plants and algae, have attracted lots of attention in biomedical and functional food science due to their significant pharmaceutical activity. In this study, four extraction methods were compared regarding the production, physicochemical properties and antioxidant activity of polysaccharides from Lepista sordida using hot water, an alkaline solution, a multiplex- enzyme method and an ultrasonic-assisted method. Methods: Bioactive polysaccharides from L. sordida were extracted using hot water, an alkaline solution, a multiplex-enzyme method and an ultrasonic-assisted method. The anthrone-sulfuric acid method was applied to measure the crude polysaccharide content and Coomassie Brilliant Blue (CBB) G-250 staining was used to detect protein content. The scavenging effect of the hydrolysates on α, α-diphenyl-β-picrylhydrazyl (DPPH) free radical was measured. Results: Polysaccharides extracted using the multiplex-enzyme method had the highest DPPH scavenging efficiency of 91.62%. The extraction efficiency of the multiplex-enzyme method was 19.61 ± 0.60%, only 1.49% lower than that of the alkaline solution method, but the polysaccharide content was 94.47 ± 3.84%, which was much higher than the 74.93 ± 5.98% obtained using the alkaline solution. The polysaccharides extracted using the multiplex-enzyme method had a low protein content. Conclusions: The multiplex-enzyme method was selected to extract the antioxidant polysaccharides of L. sordida due to a higher extraction efficiency, better purity and powerful DPPH radical scavenging ability, and lower energy consumption than the other methods. The results are of great significant for developing functional food from L. sordida bioactive polysaccharides in the future. Acknowledgments: This study was supported Guangdong Provincial College Students Innovation and Entrepreneurship Training Program (Nos. DC2016062 and DC2016063).